(untitled) (Polish Yearbook of International Law, 2024)
In the past 15 years, Georgia and Ukraine have both brought cases against Russia before the International Court of Justice (ICJ). Georgia’s 2008 application addressed the separatist movements in South Ossetia and Abkhazia. Ukraine’s 2017 case (Ukraine v. Russian Federation I) accuses Russia of discriminating against Crimean Tatars, supporting terrorism in Eastern Ukraine and downing Malaysia Airlines flight MH-17. The 2022 case (Allegations of Genocide) claims that Russia’s war against Ukraine violates the Genocide Convention. This article examines Russia’s role in these disputes, comparing outcomes in Georgia v. Russian Federation and Ukraine v. Russian Federation I, both alleging breaches of the Convention on the Elimination of All Forms of Racial Discrimination. Only the latter reached the merits phase. The article also analyses the controversial judgment on preliminary objections in Allegations of Genocide. It argues that the ICJ’s consensual jurisdiction limits its effectiveness, restricting its ability to rule on Russia’s actions against Ukraine. Additionally, it assesses Russia’s strategies in these proceedings, focussing on the “rhetorical adaptation” of international norms.